Evaluation of the American College of Sports Medicine submaximal treadmill running test for predicting VO2max - Marsh, C. E. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to assess the validity of the American College of Sports Medicine's (ACSM's) submaximal treadmill running test in predicting Vo2max. Twenty-one moderately well-trained men aged 18-34 years performed 1 maximal treadmill test to determine maximal oxygen uptake (M Vo2max) and 2 submaximal treadmill tests using 4 stages of continuous submaximal exercise. Estimated Vo2max was predicted by extrapolation to age-predicted maximal heart rate (HRmax) and calculated in 2 ways: using data from all submaximal stages between 110 b/min and 85% HRmax (P Vo2max-All), and using data from the last 2 stages only (P Vo2max-2). The measured Vo2max was overestimated by 3% on average for the group but was not significantly different to predicted VO2max (1-way analysis of variance [ANOVA] p = 0.695; M Vo2max = 53.01 ± 5.38; P Vo2max-All = 54.27 ± 7.16; P Vo2max-2 = 54.99 ± 7.69 ml/kg/min), although M Vo2max was not overestimated in all the participants—it was underestimated in 30% of observations. Pearson's correlation, standard error of estimate (SEE), and total error (E) between measured and predicted VO2max were r = 0.646, 4.35, 4.08 ml/kg-1/min (P VO2max-All) and r = 0.642, 4.21, 3.98 ml/kg/min (P VO2max-2) indicating that the accuracy in prediction (error) was very similar whether using P Vo2max-All or P VO2max-2, with up to 70% of the participants predicted scores within 1 SEE (4 ml/kg/min) of M Vo2max. In conclusion, the ACSM equation provides a reasonably good estimation of VO2max with no difference in predictive accuracy between P VO2max-2 and P VO2max-All, and hence, either approach may be equally useful in tracking an individual's aerobic fitness over time. However, if a precise knowledge of Vo2max is required, then it is recommended that this be measured directly.